Attitudinal barriers to participation in oncology clinical trials: factor analysis and correlates of barriers. (28th January 2014) - Manne, S.; Kashy, D.; Albrecht, T.; Wong, Y.‐N.; Lederman Flamm, A.; Benson, A. B.; Miller, S.M.; Fleisher, Linda; Buzaglo, J.; Roach, N.; Katz, M.; Ross, E.; et al.
<x xml:space="preserve">Abstract</x> Patient participation in cancer clinical trials is low. Little is known about attitudinal barriers to participation, particularly among patients who may be offered a trial during an imminent initial oncology consult. The aims of the present study were to confirm the presence of proposed subscales of a recently developed cancer clinical trial attitudinal barriers measure, describe the most common cancer clinical trials attitudinal barriers, and evaluate socio‐demographic, medical and financial factors associated with attitudinal barriers. A total of 1256 patients completed a survey assessing demographic factors, perceived financial burden, prior trial participation and attitudinal barriers to clinical trials participation. Results of a factor analysis did not confirm the presence of the proposed four attitudinal barriers subscale/factors. Rather, a single factor represented the best fit to the data. The most highly‐rated barriers were fear of side‐effects, worry about health insurance and efficacy concerns. Results suggested that less educated patients, patients with non‐metastatic disease, patients with no previous oncology clinical trial participation, and patients reporting greater perceived financial burden from cancer care were associated with higher barriers. These patients may need extra attention in terms of decisional support. Overall, patients with fewer personal resources (education, financial issues) report more attitudinal barriers and should be targeted for additional decisional support.